A novel route to size-controlled MIL-53(Fe) metal–organic frameworks for combined chemodynamic therapy and chemotherapy for cancer. Issue 18 (11th March 2021) - Li, Anxia; Yang, Xiaoxin; Chen, Juan
Abstract : In this study, we reported a new approach for the size-controlled synthesis of uniform iron(iii )-based MIL-53 nanocrystals using the non-ionic surfactant PVP. A combinational therapeutic approach was presented for drug delivery and ROS therapy. Abstract : Metal–organic frameworks (MOFs), such as MIL-53(Fe), have considerable potential as drug carriers in cancer treatment due to their notable characteristics, including controllable particle sizes, high catalytic activity, biocompatibility and large porosity, and are widely used in a broad range of drugs. In this study, a new approach for the synthesis of MIL-53(Fe) nanocrystals with controlled sizes has been developed using a non-ionic surfactant PVP as the conditioning and stabilizing agent, respectively. During the nucleation of MIL-53(Fe), the PVP droplet, as a nano-reactor, controlled the growth of the crystal nucleus. The size and aspect ratio (length/width) of nanocrystals increased with an increase in PVP in the synthetic mixture. The MIL-53(Fe) nanocrystals showed a homogeneous morphology, with approximately 190 nm in length and 100 nm in width. MIL-53(Fe) not only was used to load the anticancer drug doxorubicin (DOX) but also generated hydroxyl radicals (˙OH) via a Fenton-like reaction for ROS-mediated/chemo-therapy of cancer cells. The approach was expected to synthesize numerous types of nano-size iron(iii )-based MOFs, such as MIL-53, 89, 88A, 88B and 101. The MIL-53(Fe) nanocrystals hold great promise as a candidate to improve the controlled release of drugs and treatment effect for cancer therapy.